2015
DOI: 10.1002/pi.4921
|View full text |Cite
|
Sign up to set email alerts
|

Nanosilica‐immobilized UV absorber: synthesis and photostability of polyolefins

Abstract: A nanosilica-immobilized UV absorber (SiO 2 -APTMS-UVA) was prepared by the following methods: the fumed nanosilica was first modified with an aminosilane coupling agent 3-aminopropyltrimethoxysilane (APTMS) and then reacted with hydroxy-benzoyl chloride. Several measurements confirmed that the UV absorber was chemically immobilized on the surface of the nanosilica. SEM observation showed that SiO 2 -APTMS-UVA was homogeneously dispersed in the matrix of low density polyethylene (LDPE) and polypropylene (PP). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…By incorporating the DOPO‐immobilized nanosilica (5.0 wt%) into PP matrix, the thermo‐oxidative stability of PP was improved and the activation energy of the thermo‐oxidative degradation of PP was evidently enhanced. Liu et al . synthesized a nanosilica‐immobilized UV absorber (SiO 2 ‐APTMS‐UVA) by chemically grafting ortho ‐hydroxybenzoic acid onto fumed nanosilica.…”
Section: Nanosilica‐immobilized Antioxidantsmentioning
confidence: 99%
“…By incorporating the DOPO‐immobilized nanosilica (5.0 wt%) into PP matrix, the thermo‐oxidative stability of PP was improved and the activation energy of the thermo‐oxidative degradation of PP was evidently enhanced. Liu et al . synthesized a nanosilica‐immobilized UV absorber (SiO 2 ‐APTMS‐UVA) by chemically grafting ortho ‐hydroxybenzoic acid onto fumed nanosilica.…”
Section: Nanosilica‐immobilized Antioxidantsmentioning
confidence: 99%
“…As for titanium dioxide (TiO 2 ) and zinc oxide (ZnO), it was found that a photocatalytic process under sunlight may destroy the structure of binder composites with these NPs [ 18 , 19 , 20 , 21 ]. Triazine derivatives, benzotriazoles, benzophenones, and salicylates are used as organic UV absorbers, nevertheless, their thermal stability due to low molecular weight is weak [ 22 , 23 , 24 ]. However, silica NPs have some advantages such as nontoxic, non-photocatalytic, environmentally friendly, and inorganic UV shielding [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the comparable softness, ductility, and processability to LDPE make PBAT one of the promising candidates for agricultural films . However, PBAT is susceptible to ultraviolet (UV) aging , which is not acceptable for agricultural application .…”
Section: Introductionmentioning
confidence: 99%